Performance degradation assessment of the three silicon PV technologies. (3rd July 2022) - Adar, Mustapha; Najih, Youssef; Chebak, Ahmed; Mabrouki, Mustapha; Bennouna, Amin
Abstract: This study investigates seasonal performance and assesses the annual degradation rates (RD ), of three types of silicon‐based PV module technologies, using four statistical methods, namely, linear regression (LR), classical seasonal decomposition (CSD), Holt‐Winters exponential smoothing (HW), and autoregressive integrated moving average (ARIMA) on a 5‐year temperature‐corrected DC‐performance ratio time series. The lowest performance degradation rates being exhibited are found for the polycrystalline silicon (pc‐Si) system with a RD values confined between 0.23%/year and 0.36%/year. The RD values provided by the four statistical methods to the monocrystalline silicon (mc‐Si) PV modules range from 0.40%/year to 0.77%/year. The values attributed to the annual performance degradation rate of PV modules of amorphous silicon technology typically range from 0.31%/year to 0.57%/year. Abstract : Annual performance degradation rates of three PV module technologies, assessed by four statistical techniques over a 5‐year period of outdoor exposure, have shown that polycrystalline silicon technology performs best. The degradation rate has been confined between 0.42%/year and 0.55%/year for the a‐Si, 0.41%/year and 0.57%/year for the mc‐Si, and 0.14%/year and 0.16%/year for the pc‐Si. These values depend on the technique used, the seasonal behavior of PV technology, and the period of monitoring of the data used in the analysis.